Sex Differences in Immune Cell Infiltration and Hematuria in SCI-Induced Hemorrhagic Cystitis - Hadi Askarifirouzjaei; Leila Khajoueinejad; Elena Wei; Sruti Cheruvu; Carlos Ayala; Ning Chiang; Thomas Theis; Dongming Sun; Mehdi Fazeli; Wise Young (Pathophysiology, 2023)
Rats manifest a condition called hemorrhagic cystitis after spinal cord injury (SCI). The mechanism of this condition is unknown, but it is more severe in male rats than in female rats. We assessed the role of sex regarding hemorrhagic cystitis and pathological chronic changes in the bladder. We analyzed the urine of male and female Sprague-Dawley and Fischer 344 rats after experimental spinal cord contusion, including unstained microscopic inspections of the urine, differential white blood cell counts colored by the Wright stain, and total leukocyte counts using fluorescent nuclear stains. We examined bladder histological changes in acute and chronic phases of SCI, using principal component analysis (PCA) and clustered heatmaps of Pearson correlation coefficients to interpret how measured variables correlated with each other. Male rats showed a distinct pattern of macroscopic hematuria after spinal cord injury. They had higher numbers of red blood cells with significantly more leukocytes and neutrophils than female rats, particularly hypersegmented neutrophils. The histological examination of the bladders revealed a distinct line of apoptotic umbrella cells and disrupted bladder vessels early after SCI and progressive pathological changes in multiple bladder layers in the chronic phase. Multivariate analyses indicated immune cell infiltration in the bladder, especially hypersegmented neutrophils, that correlated with red blood cell counts in male rats. Our study highlights a hitherto unreported sex difference of hematuria and pathological changes in males and females’ bladders after SCI, suggesting an important role of immune cell infiltration, especially neutrophils, in SCI-induced hemorrhagic cystitis.